Investigations on the relationship between porosity and strength of admixtures modified high performance self-compacting concrete - Łaźniewska-Piekarczyk, Beata (Journal of Civil Engineering and Management, 2016)
The influence of a type of new generation: superplasticizer (SP), anti-foaming admixture (AFA) and viscosity modifying admixture (VMA) on the air-content, workability of high performance self-compacting concrete (HPSCC) is analyzed in the paper. The purpose of this study was to examine the influence of type of the admixtures on porosity of HPSCC in the aspect of the compressive strength. The research results indicated that type of admixtures and its combinations result in different strengths of HPSCC, regardless of the total porosity characteristics of HPSCC.